Effectivness of Relaxation Training on Interrelationships between Medical Students - Zahra Rajayee Zadeh; Anahita Tashk (Islamic Azad University, 2016)
Introduction: Interpersonal relationship is defined as an advanced, selective interaction between individuals. The current study aimed to explore the effect of muscle relaxation training on interpersonal relationships. Method: This quasi-experimental research was conducted on students (N=623) from the Medical University of Jiroft, south of Kerman Province in Iran. A sample of 30 available students were selected and randomly assigned into two groups: experimental and control. The experimental group received training for one month. To collect data, a self-made questionnaire on interpersonal relationship was applied. Results: Results showed that there was a significant difference between the two groups regarding pre-test and post-test scores (p<0.001). Conclusion: Findings from variance analysis and descriptive indicators revealed that